Mindful Self-Compassion Training Reduces Stress and Burnout Symptoms Among Practicing Psychologists: A Randomized Controlled Trial of a Brief Web-Based Intervention - Eriksson, Terese; Germundsjö, Linnea; Åström, Elisabeth; Rönnlund, Michael (Frontiers in Psychology, 2018)
Objective: The aims of this study were (a) to examine the effects of a 6 weeks web-based mindful self-compassion program on stress and burnout symptoms in a group of practicing psychologists, and (b) to examine relationships between changes in self-compassion and self-coldness and changes in stress and burnout symptoms. Method: In a randomized controlled trial, 101 practicing psychologists were assigned to a training group (n = 51) or a wait-list control group (n = 49). The training encompassed 15 min exercises per day, 6 days a week, for 6 weeks. The participants completed the Self-Compassion Scale (SCS), the Five Facets of Mindfulness Questionnaire (FFMQ), the Perceived Stress Scale (PSS), and the Shirom Melamed Burnout Questionnaire (SMBQ) pre and post intervention. Results: Eighty-one participants (n = 40 in the training group, n = 41 in the control group) took part in the pre and post intervention assessments. Selective gains for the intervention group were observed for SCS total scores (d = 0.86; d = 0.94 for the SCS), FFMQ scores (d = 0.60), while levels of self-coldness was reduced (d = 0.73). Critically, levels of perceived stress (d = 0.59) and burnout symptoms (d = 0.44 for SMBQ total) were additionally lowered post intervention. Finally, the results confirmed the hypothesis that the measures of distress would be more strongly related to self-coldness than self-compassion, a pattern seen in cross-sectional analyses and, for burnout, also in the longitudinal analyses. Conclusions: This training program appeared effective to increase self-compassion/reduce self-coldness, and to alleviate stress and symptoms of burnout and provide support of the distinction between self-compassion and self-coldness. Additional studies, preferably three-armed RCTs with long-term follow-up, are warranted to further evaluate the effectiveness of the program.